2011
DOI: 10.1002/chem.201101291
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐Phase Synthesis of (Poly)phosphorylated Nucleosides and Conjugates

Abstract: Succinyl-cycloSal-phosphate triesters of ribo- and 2'-deoxyribonucleosides were attached to aminomethyl polystyrene as an insoluble solid support and reacted with phosphate-containing nucleophiles yielding nucleoside di- and triphosphates, nucleoside diphosphate sugars, and dinucleoside polyphosphates in high purity after cleavage from the solid support. Here, reactive cycloSal-phosphate triesters were used as immobilized reagents that led to a generally applicable method for the efficient synthesis of phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Here, we report the synthesis of C8‐ N ‐acetyl‐ and C8‐ N H‐arylamine‐modified 2′‐deoxyguanosine‐5′‐triphosphates. The triphosphorylated adducts were synthesized by using cyclo Sal technology, which has been used successfully for the synthesis of various phosphorylated biomolecules . Conformation data on the C8‐ N ‐arylamine‐modified 2′‐deoxyguanosine‐5′‐triphosphates were collected by NOE spectroscopy and compared with DFT data.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we report the synthesis of C8‐ N ‐acetyl‐ and C8‐ N H‐arylamine‐modified 2′‐deoxyguanosine‐5′‐triphosphates. The triphosphorylated adducts were synthesized by using cyclo Sal technology, which has been used successfully for the synthesis of various phosphorylated biomolecules . Conformation data on the C8‐ N ‐arylamine‐modified 2′‐deoxyguanosine‐5′‐triphosphates were collected by NOE spectroscopy and compared with DFT data.…”
Section: Methodsmentioning
confidence: 99%
“…Mainly, the Ludwig method is used. [7][8][9][10][11][12][13] With this method the synthesis of nucleoside-5Ј-triphosphates (both natural and non-natural compounds) was accomplished in yields of up to 80 % starting from the cycloSal-compound (64 % starting from the nucleoside). This might explain the low yields that were obtained by this method.…”
Section: Introductionmentioning
confidence: 99%
“…This approach applied cleavage conditions using trifluoroacetic acid (TFA) and ammonium formate, which resulted in poor yields of the nucleoside derivatives 5 . In a separate study, Caroline et al reported the synthesis of solid phase poly-phosphorylated nucleoside analogues with decent yields and mild cleaving conditions, but extremely slow reaction times 6 . Therefore, we have explored microwave assisted solid phase nucleoside synthesis in order to optimize reaction conditions and to create a platform to perform combinatorial chemistry on solid phase nucleosides.…”
Section: Introductionmentioning
confidence: 99%